2008
DOI: 10.1007/s00216-008-2523-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of toxicity of imidazolium ionic liquids to watercress (Lepidium sativum L.)

Abstract: The sensitivity of Lepidium sativum L. germination to three imidazolium ionic liquids was investigated in solutions and soils artificially contaminated with mixtures of those compounds. In case of aquatic solutions, the toxic character of analyzed compounds is connected with their hydrophobicity. The seedling growth is increasing with the decrease in ionic liquid hydrophobicity. The novelty of those studies is the application of high-performance liquid chromatography, which was used for the determination of io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 30 publications
5
50
0
1
Order By: Relevance
“…The phytotoxicity of ionic liquids observed in the quoted studies was dependent chiefly on the applied concentration of the compound, but the factor determining the toxicity were the genetic features of the species and variety of plants used in the experiment. Matzke et al [31,38] and Studzińska and Buszewki [39] suggest also that the toxicity of ionic liquids to plants depends also on the structure of the compound and various toxic environmental factors, as well as the organic and mineral colloid contents of the soil. Cybulski et al [15] have also found that the phytotoxicity of ionic liquids is dependent on the type of cation or anion, as well as on the length of the alkyl chain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phytotoxicity of ionic liquids observed in the quoted studies was dependent chiefly on the applied concentration of the compound, but the factor determining the toxicity were the genetic features of the species and variety of plants used in the experiment. Matzke et al [31,38] and Studzińska and Buszewki [39] suggest also that the toxicity of ionic liquids to plants depends also on the structure of the compound and various toxic environmental factors, as well as the organic and mineral colloid contents of the soil. Cybulski et al [15] have also found that the phytotoxicity of ionic liquids is dependent on the type of cation or anion, as well as on the length of the alkyl chain.…”
Section: Resultsmentioning
confidence: 99%
“…With reference to this problem, along with scientific reports on the synthesis, physical and chemical properties and the potential for practical utilization of ionic liquids, a large number of studies have come up, which are concerned with the examination of the potential toxicity of these substances. Studies described in available literature reveal varied influences of ionic liquids on microorganisms [1,2,[17][18][19][20][21][22], plankton [21,[23][24][25][26], invertebrates [27][28][29], vertebrates [27,30], algae [2,21,23,29,[31][32][33], fungi [19,34,35] or higher land plants [8,21,31,[36][37][38][39]. The quoted literature shows that a likely toxic influence of a ionic liquid is determined by a number of factors, of which the primary role is played the cation type and the length of the substituent in the cation (as a rule, the longer alkyl chain, the higher toxicity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EC 50 values for germination inhibition of ChCl:Gly, ChCl:Glc were above 20,000 mg L À 1 , while the values for ChCl:OA were about 4 times lower. In general, seed germination EC 50 values for tested DESs were higher than 5000 mg L À 1 , indicating their low toxicity (Studzińska and Buszewski, 2008;Cvjetko Bubalo et al, 2014b). Furthermore, early growth of seedling was more sensitive than the seed germination since the corresponding EC 50 values for growth were at least 5.5 lower than those for germination inhibition.…”
Section: Phytotoxicity Of Dessmentioning
confidence: 95%
“…Also, the relationship study between the toxicity of the ILs and their thermodynamical properties is valuable. In particular, a close relationship between toxicity and the octanol-water partition coefficient (log P) of the IL has been found [16,17].…”
Section: Introductionmentioning
confidence: 96%